Assessment of the dose from radon and its decay products in the Bozkov dolomite cave - Navrátilová-Rovenská, Kateřina; Thinová, Lenka; Ždímal, Vladimír (Radiation protection dosimetry, 2008)
The dose from radon and its progeny remains a frequently discussed problem. ICRP 65 provides a commonly used methodology to calculate the dose from radon. Our work focuses on a cave environment and on assessing the doses in public open caves. The differences in conditions (aerosol size distribution, humidity, radon and its progeny ratio, etc.) are described by the so-called cave factor j. The cave factor is used to correct the dose for workers which is calculated using the ICRP 65 recommendation. In this work, the authors have brought together measured data of aerosol size distribution, unattached and attached fraction activity, and have calculated the so-called cave factor for the Bozkov dolomite cave environment. The dose conversion factors based on measured data and used for evaluating the cave factor were calculated by LUDEP software, which implements HRTM ICRP66.
Keywords: Ecosystem; Financing, Organized; Magnesium; Radiation Dosage; Radiation Monitoring; radon; Czech Republic; financování organizované; radiační ochrana; Occupational Exposure; pracovní expozice; ekosystém; Calcium Carbonate; hořčík; dávka záření; Česká republika; monitorování radiace; Radon; uhličitan vápenatý; Radiation Protection